Thursdays with the crown - George, Jessica Day, 1976- (Bloomsbury, 2017)
Castle Glower transports Princess Celie and her friends into a strange land where they meet two wizards, both claiming to be the Castle's original keepers. It will take luck and some magic to figure out which of them, if either at all, is telling the truth.